Pengaruh Kepemimpinan dan Iklim Kerja Terhadap Kinerja Guru SMPN di Kecamatan Pagelaran - Sri wahyuni; Siswoyo; Fatqul Hajar Aswad (Manajemen Pendidikan, 2025)
Leadership in education significantly impacts the success of educational units and students’ academic performance. Effective principals foster inclusive communication, reward achievements, and encourage teamwork, creating a motivating environment. Work climate is equally crucial, influencing teacher performance through support, communication, recognition, and access to resources, enhancing teacher motivation and satisfaction. This study examines the influence of leadership and work climate on teacher performance in public junior high schools in Pagelaran Subdistrict. Using a quantitative approach and an ex-post facto design, data were collected from teachers at SMP Negeri 1 and SMP Negeri 2 Pagelaran through purposive sampling. Analysis methods included normality, linearity, and multicollinearity tests, along with regression analyses. Findings reveal that principal leadership positively affects teacher performance (40.5%), work climate has a stronger effect (48.9%), and their combined influence contributes 49.7%. These results emphasize the importance of leadership and work climate in enhancing educational outcomes.